Pengolahan Produk Unggulan Desa dalam Upaya Meningkatkan Nilai Tambah Produk dan Meningkatkan Kemandirian Masyarakat - Rachmawati, Lucky; Suryaningsih, Sri Abidah; Fikriyah, Khusnul; Prabowo, Prayudi Setiawan (Universitas Nusantara PGRI Kediri, 2020)
The high number of poor families and the lack of employment opportunities. The solutions offered are training in processing superior products, thus opening up new job opportunities and motivating the community to be independent. One of the potential possessed by Wonosalam Subdistrict is cow milk production. To increase the added value of dairy products in this area, we carry out a training to process superior products in Wonosalam District. The output of this PKM activity is the creation of a superior village product in the form of Jackfruit Milk Pie. Jackfruit milk pie made from milk and jackfruit. The object of this training is the female population both classified as working age (15-64) and outside of working age (64+). For women who are of working age, this activity will provide business opportunities for them, so they can try to be independent. For female residents outside the working age will motivate them to work, thereby reducing the burden of family dependence.